2014
DOI: 10.1111/aas.12360
|View full text |Cite
|
Sign up to set email alerts
|

Major complications of epidural anesthesia: a prospective study of 5083 cases at a single hospital

Abstract: Serious complications were very rare; only one patient had permanent sequelae, and a single epidural hematoma was diagnosed. Post-operative neurologic deficits were more common, but most complications resolved spontaneously within 3 months and they rarely required intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 29 publications
2
34
1
3
Order By: Relevance
“…Epidural hematoma is a rare but dreaded complication of neuraxial techniques, with an incidence around 1:150,000 after epidural anesthesia . We did not observe any case of spinal hematoma in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Epidural hematoma is a rare but dreaded complication of neuraxial techniques, with an incidence around 1:150,000 after epidural anesthesia . We did not observe any case of spinal hematoma in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Permanent injury to the spinal cord or spinal nerves is a serious complication that can occur with neuraxial anesthesia; however, it is exceedingly rare, with a reported incidence of <4 in 100,000 30 . Transient postoperative neurologic deficits and postdural puncture headache are also associated with the use of spinal anesthesia 31,32 . This study was limited by the characteristics of the ACS-NSQIP database.…”
Section: Discussionmentioning
confidence: 99%
“…6,[9][10][11][12][15][16][17][18][25][26][27][28][29][30][31][32][33][34][35] Some studies report high incidences, in the range of 20-37 events per 100,000 catheterizations. 9,11,26,28 Nevertheless, these studies have a common weakness, that is, a relatively small sample size. The inci-dence of spinal hematoma in non-obstetric EA found in our study (18.5 per 100,000) is consistent with studies including large sample size, which have reported incidences of spinal hematoma in the range of 11-19 per 100,000 catheterizations.…”
Section: Discussionmentioning
confidence: 99%